Seed Science Research: Volume 8 p. 1-74, September 1998, Supplement No. 1 Ultra-Dry Seed Storage, CABI/IPGRI Joint Publication - Black, M.; Walters, C.; Cohn, M.A. (1998)
Seed Science Research provides an international vehicle for the publication or original papers and review articles on the fundamental aspects of seed research. The emphasis is on the physiology, biochemistry, molecular biology and ecology of seeds.Storage of seed at low temperature is the main ex situ conservation method employed in genebanks. The recommended preferred conditions for long-term seed storage, according to the Genebank Standards published in 1994 by FAO and the International Plant Genetic Resources Institute (IPGRI), are 3-7% seed moisture content, depending on the species, at - 18°C or cooler. In the late 1980s, systematic research was initiated by the International Board for Plant Genetic Resources (IBPGR, now IPGRI) to investigate the effects of very low moisture content on seed longevity. Much of this research was based on the general assumption that the relative benefit in terms of longevity became greater for each successive reduction in seed moisture content, although this may vary among species. One of the most compelling reasons for undertaking research in this area was the prospect of developing 'low-input' alternatives for medium- to long-term cold storage of seed germplasm through its storage at room temperature (i.e. ultra-dry seed storage). Such an approach, it was believed, would allow for a secure and cost-efficient alternative for seed storage in cases where a reliable supply of electricity is not available for refrigeration of storage rooms. In line with its objectives to develop and broaden the applicability of conservation techniques, IPGRI actively supported research activities in this area, including significant work conducted in research institutes and genebanks in China. To make appropriate recommendations to the plant genetic resources community, in particular regarding the applicability of the ultra-dry seed technology, it was deemed necessary to resolve the basic questions of the optimal seed moisture level in relation to storage temperature, including the possibility of over-drying the seeds. It was in recognition of this need that IPGRI initiated the global ultra-dry seed storage experiment in 1995. During the Second International Conference on Seed Science and Technology, Guangzhou, China, 12-16 May 1997, a Satellite Symposium on ultra-dry seed storage and longevity was organized by IPGRI to assess the current state of the art in this research area.